Petty Cash Management Analysis on Small and Medium Micro Enterprises (Study at MSME Pemuda Grafika Selayar) - Asrijal Akib; Ari Utomo Saputra; Amar Ma’Ruf Al-Mubaroq; Bondo (Medikun Publisher, 2024)
Petty cash is the amount of cash held by a business held or managed by an employee, the treasurer whose duty is to pay or finance expenses that are usually small, regular, and immediate. The object of this research is one of the MSME located on the island of Selayar, the small MSME cash is handled by a cashier, but there are still gaps in the recording process. The aim of this study is to study how the use of small cash in a small and medium-sized micro enterprise (MSME) thus makes a good contribution to the sustainability of the enterprise. The method used in this research is qualitative descriptive method. The results of the research show that the use of petty cash in small and medium-sized micro enterprise is very supportive for business sustainability but there are still shortcomings found in small cash management at MSME i.e. in the cash control system